Verifiability on the run: an experimental study on the verifiability approach to malingered symptoms - Boskovic, Irena (Psychiatr Psychol Law, 2018)
Several studies on the verifiability approach found that truth-tellers report more verifiable details than liars. Therefore, we wanted to test whether such a difference would emerge in the context of malingered symptoms. We obtained statements from undergraduates (N = 53) who had been allocated to three different conditions: truth-tellers, coached malingerers and naïve malingerers. Truth-tellers carried out an intensive physical exercise and after a short interval wrote a report about their experience and elicited symptoms. The two malingering groups had to fabricate a story about the physical activity and its symptoms. Truth-tellers did not generate more verifiable details than malingerers. However, malingerers reported more non-verifiable details than truth-tellers. Coached and naïve malingerers did not differ in this respect. Relative to truth-tellers, naïve malingerers reported more symptoms-related non-verifiable details, while coached malingerers reported more exercise-related non-verifiable details. Focusing on non-verifiable details may inform the detection of malingered symptoms.